In the Web of Class Delinquents and Reformers in Boston, 1810s-1930s - Schneider, Eric C. 1951-2017 (New York University Press, 1993)
"An analytic overview of the history of social welfare and juvenile justice in Boston..[Schneider] traces cogently the origins, development, and ultimate failure of Protestant and Catholic reformers' efforts to ameliorate working-class poverty and juvenile delinquency."-Choice"Anyone who wants to understand why America's approach to juvenile justice doesn't work should read In the Web of Class."-Michael B. Katz,University of Pennsylvania
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jun 2020)
Keywords: HISTORY / United States / State & Local / General; Child welfare -- Massachusetts -- Boston -- History; Juvenile corrections -- Massachusetts -- Boston -- History; Poor children -- Massachusetts -- Boston -- Social conditions; Social work with juvenile delinquents -- Massachusetts -- Boston -- History